2019
DOI: 10.4314/jab.v129i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Détermination du niveau de contamination et de l’apport en résidus de tylosines (macrolides) des oeufs de consommation dans le District d’Abidjan (Côte d’Ivoire)

Abstract: Détermination du niveau de contamination et de l'apport en résidus de tylosines (macrolides) des oeufs de consommation dans le District d'Abidjan (Côte d'Ivoire)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…For example, FAGBAMILA et al [11] in Nigeria reported that out of 900 egg samples analyzed using the disk diffusion test, 32 (3.6%) contained antibiotic residues and 18 eggs (2%) gave positive results with the Premi ®Test method. In Senegal, the presence of antibiotic residues was qualitatively confirmed in eggs at 12% [12].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, FAGBAMILA et al [11] in Nigeria reported that out of 900 egg samples analyzed using the disk diffusion test, 32 (3.6%) contained antibiotic residues and 18 eggs (2%) gave positive results with the Premi ®Test method. In Senegal, the presence of antibiotic residues was qualitatively confirmed in eggs at 12% [12].…”
Section: Discussionmentioning
confidence: 88%
“…A study conducted in Ivory Coast showed the presence of residues in almost 26% of table egg samples tested [12].…”
Section: Discussionmentioning
confidence: 99%
“…The hazard ratio was carried out by comparing the estimated doses of AFB1 and AFT with the values of the maximum reference concentrations [20]. The proportions obtained were compared to 1 [21].…”
Section: Determination Of the Hazard Ratio (Hr)mentioning
confidence: 99%
“…They are composed of carbon atoms forming benzene rings (2 to 10) and hydrogen atoms [1]. Among these molecules, sixteen (16) have been prioritized by the United States Environmental Protection Agency (US-EPA) due to their abundance in the environment and/or their extensive use by industry. The fear caused by PAHs comes from the fact that they are contaminants resulting from combustion processes and some of these molecules are considered potentially carcinogenic, including Benzo (a) Pyrene [2].…”
Section: Introductionmentioning
confidence: 99%
“…The fear caused by PAHs comes from the fact that they are contaminants resulting from combustion processes and some of these molecules are considered potentially carcinogenic, including Benzo (a) Pyrene [2]. However, the World Health Organization (WHO) proposes to monitor mainly six (6) of the sixteen (16) PAH molecules that are considered as priorities because of their harmful effects on the environment and their high toxicity [3]. These are Benzo (a) Pyrene, Fluoranthene, Benzo (a) Fluoranthene, Dibenzo (ah) Anthracene, Benzo (k) Fluoranthene, Benzo (g,h,i) Perylene and Indeno (1,2,3-cd) Pyrene.…”
Section: Introductionmentioning
confidence: 99%